Fatores que influenciam na aprendizagem escolar do aluno, na visão da família e da sociedade com as perspectivas da escola de tempo integral: desafios e possibilidades - Paiva, Maria Estelisa Ramos da Costa (2024)
Full-time education has been presented in today's society as a public policy of great relevance and an essential instrument of action, a way of alleviating social inequalities through expanded learning. The research evaluates the Public Educational Policy for full-time education in schools in the municipality of Maracanaú-Ce, presenting a discussion on the factors that influence the academic learning of students at the Full-Time School (Ferreira, 2015; Jacomeli, 2010). By exposing some policy concepts, we present the format of public policies in Brazil, from its origins to the present day (Silva, 2016; Bacelar, 2003). Social policies must work to combat poverty, inequality, income generation, encouraging social interaction and the well being of society (Saviani, 2008; 2011; Fonseca; Fagnani, 2023). In this research, with a qualitative approach, we aim to evaluate how the Public Policy for Full-Time Education can contribute to the learning of children and adolescents in the municipality of Maracanaú. In the study, our methodological procedure was documentary analysis, such as Laws, Decrees, Pedagogical Political Projects, academic productions on the subject and semi-structured interviews with managers, parents and teachers from two full-time schools in the city of Maracanaú. To this end, the in-depth assessment based on Rodrigues (2008, 2016) and Gussi; Oliveira (2016) outlined the evaluative perspective of the research. The data collected in the field regarding the factors that influence learning made it possible to identify several factors that function as a chain of problems that expand, causing many gaps in various areas of society, especially in education. In relation to teachers, it was possible to conclude that a very important factor is the training of teachers, managers and employees in the implementation of full-time schools, which needs to be thought of concomitantly with a conception of integral education, covering the way in which work, with a view to expanding meaningful and emancipatory learning opportunities for students.